Introduction to the Dinaric Karst - Zupan Hajna, Nadja; Mihevc, Andrej; Prelovšek, Mitja (ZRC SAZU, Založba ZRC, 2010)
Dinaric karst is expansive, 800 km long and up to 150 km wide area of karst, which extends over majority of Dinaric mountains and therefore also over the southwestern part of Slovenia. Dinaric karst is an important karst area with remarkable caves, big sinking streams and abundant karst springs. Well-expresed karst phenomena of Dinaric karst lead to early descriptions and karstological investigations. During the 19th century, a term karst was for the first time used for description of specific area without a superficial drainage system. Some Slavic words for relief forms (doline, polje, uvala, ponor) became world-wide terms. Dinaric karst is also a place of first descriptions of troglobionts. In spite of many other karst areas investigated all over the world Dinaric karst still remains one of the most important karst areas. Dinaric karst is locus tipicus of many features and phenomena. It is place of deep scientific investigation and also the place, where karstologists from all over the globe meet together. Publication in popular science language describes the basic characteristics of Dinaric karst and Slovene examples of relief types in the Dinaric karst area.